ANALISIS ISU-ISU KRITIS PENDIDIKAN ISLAM DALAM KONTEKS MODERASI BERAGAMA DI INDONESIA : Tinjauan terhadap Implementasi Kurikulum dan Peran Institusi Pendidikan - Tuti, Hastuti; Usman, Syahruddin; Ondeng, Syahruddin (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
This study explores the major challenges in Islamic education in Indonesia, focusing on religious moderation. The research primarily examines how the curriculum is implemented and the role of Islamic educational institutions in supporting religious moderation. Using a qualitative approach and case studies of several Islamic educational institutions, data were collected through interviews, observations, and document analysis. The findings indicate that despite efforts to incorporate the values of religious moderation into the curriculum, numerous obstacles remain, such as resource limitations, resistance from certain groups, and differing views on the concept of religious moderation. Islamic educational institutions play a crucial role in shaping students' understanding of religious moderation, but their effectiveness heavily depends on the dedication and capacity of educators, as well as support from the government and the community. This study recommends enhancing educators' capacities, improving curriculum quality, and fostering stronger collaboration between the government, educational institutions, and the community to achieve the goals of religious moderation in Islamic education. These findings are expected to contribute to the development of more inclusive and tolerant educational policies in Indonesia.